Correlation between the ibopamine provocative test and the diurnal tension curve in glaucoma patients - Magacho,Leopoldo (2006)
PURPOSE: To correlate the ibopamine provocative test with the diurnal tension curve (highest intraocular pressure-IOP and range) in glaucoma. METHODS: This is a prospective case series including glaucoma patients from the Federal University of Goiás, Glaucoma Service. Two 2% ibopamine eyedrops were instilled into one or both eyes of each patient, 5 minutes apart. Intraocular pressure was checked before and 30 and 45 minutes after the second ibopamine instillation. Thereafter, the diurnal tension curve of each patient was assessed with five independent measurements (at every 2:30 hours), from 8:00 o'clock AM to 6:00 o'clock PM. Pearson's correlation coefficient was used to test the linear relation between the intraocular pressure after the ibopamine instillation with the highest intraocular pressure value and the intraocular pressure range in the diurnal curve. RESULTS: Thirty-one eyes from 22 patients were included. There was a significant correlation between the intraocular pressure 30 and 45 minutes after ibopamine instillation and the highest intraocular pressure assessed in the diurnal curve (r=0.356, p=0.04 and r=0.429, p=0.01, respectively). However, no correlation between IOP after the use of ibopamine and the diurnal intraocular pressure range at 30 (r=0.046, p=0.8) and 45 minutes (r=0.109, p=0.5) was observed. CONCLUSION: The ibopamine provocative test shows a significant correlation with the highest intraocular pressure in the diurnal tension curve in glaucoma patients. However, no correlation was observed with the intraocular pressure range.